Charakterystyka prawna i społeczna „dobra" zakładu pracy - Chobot, Andrzej (Wydział Prawa i Administracji UAM, 1984)
A notion of „benefit" of establishment is related to a legal construction constituting an element of legal institution: care for the interest of establishment what in turn is linked with a basic principle of labor law (art. 12 of labor code, hereinafter called l.c.) and one of the basic duties of labor (art. 100 § 2 p. 5 l.c.). Although the legislator does not define that notion directly, but the way of its determination is indicated indirectly. The detailed study of the regulation, doctrinal findings and axiological premises results in a conclusion that a legal concept of „benefit" of enterprise is related to philosophical concepts of common good and to the vision of social reality adopted by the so called structural functionalism. A general feature of the benefit the regulation is referring to, is, among others, undisturbed, harmonious functioning of establishment in the process of reaching its productive effect, sui generis a state of dynamic equilibrium. Philosophers would speak in that instance of peace or social order. Common good has first of all a personal character (the ethical and ontological scope), its material character is revealed only in its instrumental aspect. Consequently, it is necessary to depart from such notion of „benefit" of establishment which would bring only material associations. It can also be more proper to use a term of benefit of „labor community" or, at least, „benefit of employer". It is labor community (and not objectified set of production factors) which maintains operation of establishment as a whole. The principle of analogy and proportionality of common good is guaranteed and realized by labor law by means of a double conditioning of emploees' duty to care for the interest („benefit") of establishment. A need of removing interferences in operation of establishment (the element of analogy) gives rise to that duty, unless the events related to a socially justified individual interest of an emploee occur (the element of proportionality) barring that duty in spite of a materialized condition on the part of establishment. Philosophers also maintain that a common interest can dominate over individual values only when it is the case of equal good, and not in the situation when an individual interest is ranking higher. In" the legal construction it is realized in the priority of socially valid individual interest of an emploee over the benefit of establishment, in particular, interests related to the existence and developement of an individual or to functioning of family group take precedence of it.
Legal and social characteristics of "the benefit" of establishment